Leaving the House - Pickford, Joel:::::::::
Glenna and Rollin leave the Pipes house on the way to their honeymoon. The house was built in 1939 by Glenna's father, Loren Beryl Pipes, using a substantial amount of material left over from his other contracting projects. The design is partly inspired by George Washington's home at Mount Vernon, VA.